Immunization during pregnancy: do healthcare workers recommend vaccination against influenza? - Licata, Francesca; Pelullo, Concetta Paola; Della Polla, Giorgia; Citrino, Emma Antonia; Bianco, Aida (Frontiers in Public Health, 2023)
Background: A variety of circumstances can influence how widely vaccination during pregnancy is accepted. Health care workers (HCWs) are often seen as the main resource for recommending vaccination. The purpose of the current study was to determine whether Italian HCWs advise and recommend pregnant people to receive the influenza and COVID-19 vaccinations, as well as what knowledge and attitudes affect their practices. Methods: This cross-sectional study, took place between August 2021 and June 2022 in a randomly selected sample of HCWs in three Italian regions. The target population comprised obstetricians-gynecologists, midwives and primary care physicians, who provide medical care to pregnant people. The questionnaire consisted of 19 items divided into 5 parts gathered information about the participants' sociodemographic and professional characteristics, general knowledge about vaccinations during pregnancy, and vaccine-preventable diseases (VPDs), attitudes and practices towards immunization, and strategies to potentially increase vaccination uptake during pregnancy. Results: Among the participants, 78.3% that pregnant people are at increased risk of severe complications from influenza and 57.8% that the influenza vaccine is not provided only in the 2nd/3rd trimester of pregnancy. Only 68.8% recommended getting vaccinated against influenza. Of the enrolled HCWs, 10.8% believed that the potential risks of vaccines administered during pregnancy are greater than the benefits. An even higher proportion of the participants was unsure (24.3%) or did not deem (15.9%) that vaccinating against influenza during pregnancy reduces the risk of preterm birth and abortion. Seven out of ten HCWs advised women about influenza vaccination during pregnancy, and 68.8% recommended getting vaccinated against influenza during pregnancy. Results showed that good knowledge and positive attitudes were the strongest factors positively associated with advising women about influenza vaccination during pregnancy. Conclusions: The gathered data showed that a sizable portion of the HCWs lacks up-to-date knowledge, underestimates the risks of contracting a VPD, and overestimates the risks of vaccine side effects. The findings shed light on such attributes useful to promote adherence to evidence-based recommendations by HCWs.